The Effect of the Microsoft Excel based Interactive Learning Media on the Physics Problem Solving - Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi (Indonesian Review of Physics (IRiP), 2018)
The physics problem solving is needed students to overcome the phenomenon of physics.Â  The development of technology in physics learning is able to explain the concept of abstract physics. This study aims to know effect of use interactive learning media based Microsoft Excel on the physics problem solving. The subject on this media is Heat and Temperature. The research method used is pretest-postest controlled group design. The analysis technique is used t-test with SPSS 16.0 with a margin of error of 5%. The results of this study showed that the mean scores of post-test treatment class students significantly better than the average score post-test control class indicated by the average score of students' post-test treatment class at 80.26 and scores the average post-test control class at 68.00 and with SPSS analyze sig value is 0.000. While the average score gain results-physics students learn physics class treatment significantly better than the average score gain results Physics students learn physics-control class indicated by the average score of physics problem solving gain of 0.77 and the treatment class the average score gain control class student physics problem solving of 0.63.